Particulate matter 2.5 pollution, perception, and mental stress - Khanthavit, Raabkwan; Khanthavit, Anya (Intelektual Pustaka Media Utama, 2025)
Multivariate mediation analyses were used to relate perceptions of particulate matter 2.5 (PM2.5) pollution level directly and indirectly to mental stress of residents in Bangkok, Thailand. PM2.5 induced concerns about respiratory and cardiovascular diseases, health, and unemployment served as mediators of the indirect effects. This study decomposed full perception into correct perception (actual PM2.5 level) and misperception so that the effects of perception and its components can be examined separately. The data were daily time series, beginning July 30, 2016, and ending September 30, 2023. Unobserved perception, PM2.5 induced concerns, and mental stress were proxied by Google’s relative search volume indexes. Correct perception was the actual PM2.5, whereas misperception was the regression residual of the full perception on the actual PM2.5. In the full sample, full perception and misperception had significant indirect effects, whereas correct perception had a significant direct effect. Respiratory disease was the main contributor to the significant indirect effect, although concern itself was not significant. For the COVID-19 subsample, full perceptions showed significant total, direct, and indirect effects. The significant indirect effect was explained by concerns regarding respiratory diseases and health. Correct perception had a significant direct effect; its indirect effect was small and nonsignificant. The results for misperceptions were similar to those for perceptions.